ANALISA PENGELOLAAN KINERJA APARATUR SIPIL NEGARA PADA KANTOR CAMAT KECAMATAN DARUL HASANAH KABUPATEN ACEH TENGGARA - Rila Fatmawati; Rila Maufira; Edi Jamaris (CV. Armas Suan Sejahtera, 2026)
This qualitative descriptive study was conducted to identify measurable performance targets and examine work activities aimed at enhancing the professionalism and competence of Civil Servants (ASN) at the Darul Hasanah Subdistrict Office, Aceh Tenggara Regency. Data was collected through observation, interviews, and documentation. The Darul Hasanah Subdistrict Office currently employs 25 staff members. The educational profile reveals a non-optimal distribution, consisting of 1 postgraduate, 12 bachelor's degree holders (S1), and 22 high school or equivalent graduates. The research confirms that performance targets have been clearly defined using the Key Performance Indicators (IKU) of the subdistrict. Furthermore, the overall performance of the ASN in relation to work targets considering factors like quantity, time, and cost is deemed satisfactory and aligns with their established duties and functions.Despite the satisfactory performance against targets, the study highlights several areas requiring improvement. Key findings suggest that the quality of human resources is not yet optimal, specifically concerning employee discipline. While service orientation is defined in the IKU, the ASN’s performance is constrained by inadequate facilities and infrastructure. Based on these conclusions, the study offers several recommendations. The leadership must demonstrate a direct commitment to resolving internal issues and actively seek solutions to support performance management. Specifically, it is recommended that disciplinary measures be applied to employees who consistently fail to comply with work schedules. Finally, a restructuring of employee numbers should be implemented to ensure alignment between staff capacity, workload, and working hour requirements, thereby optimizing efficiency